2014
DOI: 10.1212/wnl.0000000000000666
|View full text |Cite
|
Sign up to set email alerts
|

White matter correlates of cognitive dysfunction after mild traumatic brain injury

Abstract: Acute mild/moderate traumatic brain injury is characterized by increased tissue FA, which represents a clear neurobiological link between cognitive dysfunction and white matter injury after mild/moderate injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 40 publications
(41 reference statements)
7
59
3
1
Order By: Relevance
“…Only few studies looked at the correlation between changes in the brain and changes in cognition over a long time period (Croall et al, 2014). Above, we showed a longitudinal increase in functional connectivity within the DM-like subnetwork in patients interpreted as reflecting recovery, which therefore may be linked to cognitive improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies looked at the correlation between changes in the brain and changes in cognition over a long time period (Croall et al, 2014). Above, we showed a longitudinal increase in functional connectivity within the DM-like subnetwork in patients interpreted as reflecting recovery, which therefore may be linked to cognitive improvement.…”
Section: Discussionmentioning
confidence: 99%
“…stroke, small vessel disease, multiple sclerosis, amyotrophic lateral sclerosis and traumatic brain injury. 10,11,26,[29][30][31][32] On the other hand, a limited number of studies have reported an FA increase. These could previously be divided into two pathophysiological categories.…”
Section: Discussionmentioning
confidence: 99%
“…Проте великі надії покладаються на прижиттєву візуалізацію накопичень τ-білка та β-амілоїда за допомогою позитронно-е-місійної томографії [41,42], а також дифу-зійно-тензорної томографії (diffuse tensor imaging). Останній метод дає змогу визна-чити зміни розподілу води у білій речовині головного мозку внаслідок її пошкодження і виявився достатньо чутливим для діагнос-тики легкої ЧМТ [43]. Крім ХТЕ, результати аналізу посмертних зразків головного мозку свідчать про підвищений ризик ХА та ХТЕ.…”
Section: нейродегенеративні патології як наслідок легкої чмтunclassified